Korean Red Ginseng water extract inhibits COX-2 expression by suppressing p38 in acrolein-treated human endothelial cells - Seung Eun Lee; Yong Seek Park (Journal of Ginseng Research, 2014)
Cigarette smoke is considered a major risk factor for vascular diseases. There are many toxic compounds in cigarette smoke, including acrolein and other α,β-unsaturated aldehydes, which are regarded as mediators of inflammation and vascular dysfunction. Furthermore, recent studies have revealed that acrolein, an α,β-unsaturated aldehyde in cigarette smoke, induces inflammatory mediator expression, which is known to be related to vascular diseases. In this study, we investigated whether Korean Red Ginseng (KRG) water extract suppressed acrolein-induced cyclooxygenase (COX)-2 expression in human umbilical vein endothelial cells (HUVECs). Acrolein-induced COX-2 expression was accompanied by increased levels of phosphorylated p38 in HUVECs and KRG inhibited COX-2 expression in HUVECs. These results suggest that KRG suppresses acrolein-induced COX-2 expression via inhibition of the p38 mitogen-activated protein kinase signaling pathway. In addition, KRG exhibited an inhibitory effect on acrolein-induced apoptosis, as demonstrated by annexin V–propidium iodide staining and terminal deoxynucleotidyl transferase-mediated dUTP nick end-labeling assay. Consistent with these results, KRG may exert a vasculoprotective effect through inhibition of COX-2 expression in acrolein-stimulated human endothelial cells.